2009
DOI: 10.1371/journal.ppat.1000252
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Influenza Virus in a Mammalian Host Is Increased by PB2 Amino Acids 627K or 627E/701N

Abstract: Since 2003, more than 380 cases of H5N1 influenza virus infection of humans have been reported. Although the resultant disease in these cases was often severe or fatal, transmission of avian influenza viruses between humans is rare. The precise nature of the barrier blocking human-to-human spread is unknown. It is clear, however, that efficient human-to-human transmission of an antigenically novel influenza virus would result in a pandemic. Influenza viruses with changes at amino acids 627 or 701 of the PB2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
499
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(515 citation statements)
references
References 30 publications
(56 reference statements)
16
499
0
Order By: Relevance
“…Several amino acid changes in PB2 are important for the replication or virulence of influenza viruses in mammals (22)(23)(24)(25)(26)(27)(28)(29)(30). A detailed comparison of the amino acid differences among the EAH1N1 SIVs indicated that all of these viruses have mammalian-adapting mutations in their PB2 genes (SI Appendix, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Several amino acid changes in PB2 are important for the replication or virulence of influenza viruses in mammals (22)(23)(24)(25)(26)(27)(28)(29)(30). A detailed comparison of the amino acid differences among the EAH1N1 SIVs indicated that all of these viruses have mammalian-adapting mutations in their PB2 genes (SI Appendix, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Discrete mutations within the polymerase have also been associated with an extended host range. A notable example is the species-specific preference for lysine at PB2 position 627 resulting in high levels of viral replication and/or polymerase activity in animal models and human cells (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Other changes within PB2, such as the D701N mutation, are associated with increased host range, polymerase activity, and pathogenicity in mammalian systems and humans (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…PB2 derived from human viral isolates almost exclusively possesses a lysine at position 627 (K627), whereas glutamic acid (E627) at this position predominates in avian viruses (6). PB2 K627 correlates with enhanced polymerase activity, virus replication, transmission, and in certain cases, pathogenicity and mortality in mammals (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). PB2 K627 also correlates with moderately enhanced influenza virus replication in pigs, consistent with pigs serving as an intermediary viral reservoir between birds and humans (17).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…4F and when comparing the viral titers and length of shedding in respiratory droplet contacts from RCP10 and 2RCP10:6M98. The internal genes have been implicated in transmission not only within avian species (20)(21)(22) but also from avian to mammalian species (23,24). A complete set of viruses tested and their transmission phenotype are listed (Table 4 and supporting information (SI) Fig.…”
Section: Adaptive Mutations On Rcp10 Surface Proteins Support Respiramentioning
confidence: 99%